Analisis Kendala Implementasi Marketplace Pemerintah dan Digital Payment Dalam Pemberdayaan UMKM - -, Istianah (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2021)
The government has launched the Government Marketplace and digital Payment with the main objective of encouraging efficiency, effectiveness, transparency and accountability of state spending, as well as empowering vendors, most of whom are MSMEs. Here the government integrates the working unit of APBN users, MSMEs as providers of goods/services, and banking in one ecosystem. 3 Government banks have been selected as platform providers with Digital Payment (Digipay) applications. Digipay has been designed in such a way to make it easier for users but users are still reluctant to use it.